Mesenchymal stem cells exert anti-proliferative effect on lipopolysaccharide-stimulated BV2 microglia by reducing tumour necrosis factor-α levels - Jose, Shinsmon; Tan, Shi Wei; Ooi, Yin Yin; Ramasamy, Rajesh; Vidyadaran, Sharmili (BioMed Central, 2014)
Background Progression of neurodegenerative diseases occurs when microglia, upon persistent activation, perpetuate a cycle of damage in the central nervous system. Use of mesenchymal stem cells (MSC) has been suggested as an approach to manage microglia activation based on their immunomodulatory functions. In the present study, we describe the mechanism through which bone marrow-derived MSC modulate the proliferative responses of lipopolysaccharide-stimulated BV2 microglia. Methods BV2 microglia were cultured with MSC and stimulated with 1 μg/ml lipopolysaccharide. Using an inducible nitric oxide synthase inhibitor, tritiated thymidine (3H-TdR) incorporation assay was performed to determine the role of nitric oxide in the anti-proliferative effect of MSC. We also studied apoptosis and the cell cycle of both cell types using flow cytometry and explored their cytokine profile using protein and cytometric arrays. Moreover, the role of IL-6 and TNF-α in immunomodulation was deduced using specific blocking antibodies and recombinant proteins. Results MSC reduces microglia proliferation upon lipopolysaccharide stimulation by 21 to 28% and modulates the levels of nitric oxide, IL-6 and TNF-α. The role of nitric oxide in conferring the anti-proliferative effect of MSC was ruled out. Furthermore, we found that MSC exert their anti-proliferative effect by restoring the percentage of BV2 cells at S and G2/M phase to levels similar to unstimulated cells. MSC undergo a G0/G1 arrest while exerting this effect. We have also identified that MSC-mediated modulation of microglia is independent of IL-6, whilst reduction of TNF-α in co-culture is critical for inhibition of microglia proliferation. Conclusions Our study demonstrates that MSC inhibit microglia proliferation independent of nitric oxide and IL-6, although reduction of TNF-α is critical for this effect. The inhibition of proliferation is through cell cycle modulation. These findings shed light on the mechanisms of microglial immunomodulation by MSC.